Antioxidant supplements relieve insulin resistance but do not improve lipid metabolism in women with polycystic ovary syndrome: a meta-analysis of randomized clinical trials - Ruye Wang; Chenyun Miao; Yun Chen; Ying Zhao; Liuqing Yang; Wei Cheng; Qin Zhang (Gynecological Endocrinology, 2022)
Objective: The effect of antioxidant supplements on glucose metabolism and lipid profiles in polycystic ovary syndrome (PCOS) remains controversial. This systematic review and meta-analysis aimed to evaluate whether antioxidant supplements improve glucose metabolism and lipid profiles in women with PCOS to provide optimal nutritional supplement advice in clinical practice. Methods: The search was conducted across multiple medical databases from inception to January 1, 2022 and performed following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. A random effects model was used to calculate the overall effects. Results: Eighteen trials (1113 participants) were included. Antioxidant supplements significantly improved insulin resistance (95% CI, −0.62, −0.30; p < 0.00001; I2 =48%), fasting insulin (95% CI, −0.80, −0.44; p < 0.00001; I2 = 48%), and fasting plasma glucose (95% CI, −0.54, −0.21; p < 0.00001; I2 = 38%) in patients with PCOS. However, antioxidant supplements were found to not improve most indices of lipid profiles in PCOS except triglyceride. Conclusions: Antioxidant supplements are an effective intervention for relieving insulin resistance but do not significantly improve lipid metabolism in women with PCOS.